KARAKTERISTIK FISIK SABUN SUSU DENGAN PENAMBAHAN EKSTRAK KULIT KAYU MANIS - Putri, Afmi; Monica, Metha; Fatati, Fatati (PT. Hasba Edukasi Mandiri, 2025)
This study aimed to determine the physical characteristics of milk soap with the addition of cinnamon bark extract, focusing on pH, moisture content, and foam stability. The research was conducted at the Laboratory of the Faculty of Animal Science, University of Jambi, from June 6 to July 21, 2024. The soap was formulated using fresh cow’s milk, coconut oil, palm oil, NaOH, and cinnamon bark extract. Treatments consisted of P0 = 0% (control), P1 = 2%, P2 = 4%, P3 = 6%, and P4 = 8% cinnamon bark extract. A Completely Randomized Design (CRD) with five treatments and four replications was applied. Observations included pH, moisture content, and foam stability. The results showed pH values ranging from 10.07 to 10.63, moisture content from 5.80% to 9.46%, and foam stability from 39.34% to 44.40%. Statistical analysis indicated that the addition of cinnamon bark extract had no significant effect (P>0.05) on all observed parameters. Therefore, it can be concluded that up to 4% cinnamon bark extract can be added in milk soap formulation without significantly affecting its physical properties. All tested parameters remained within acceptable quality standards for solid soap in terms of functionality and sensory acceptance.